Decarbonization in state-owned power companies: Lessons from a comparative analysis. (25th June 2022) - Benoit, Philippe; Clark, Alex; Schwarz, Moritz; Dibley, Arjuna
Abstract: A rapid decarbonization of the electricity system is urgently required for the Paris Agreement objectives to stand a reasonable chance of being met. While state-owned power companies (SPCs) are the dominant firm type in the global electricity sector, representing nearly two thirds of global electric power generation capacity, most climate policy literature focuses on private sector companies when analyzing decarbonization interventions. SPCs' distinct corporate governance structures, objectives, relationships with government, and sources of finance, however, can be markedly different from those of private companies. Here, we develop a framework for analyzing the extent to which common and divergent features of SPCs, and the markets in which they operate, affect their relationship to government interventions on decarbonization. We also consider the implications of these relationships for the effective implementation of sector-wide decarbonization strategies. We then apply this framework using a comparative case study analysis of six major SPCs, and highlight how differences in their agency, motivation, capacity, and market exposure may result in different potential responsiveness to government regulatory, policy and market interventions on decarbonization. We generalize these findings by developing four SPC archetypes and illustrate how they might respond differently to government interventions targeting decarbonization. Our analysis posits that SPCs can, under the guidance of governments pursuing ambitious climate policy, be more effective vehicles for decarbonization relative to private sector companies, particularly when they operate with a high degree of operational independence, are insulated from competitive pressures, and have the financial and technical capacity to invest in the decarbonization of their asset base. Similarly, market-wide policy interventions, such as carbon pricing mechanisms, could in practice be less effective interventions with respect to SPCs than their private counterparts when the SPC is ill-equipped to translate these incentives into decarbonization action because it is mandated to pursue supplementary objectives other than profit maximization alone. Ultimately, governments will need to step up their climate action to achieve carbon neutrality. SPCs can, and where they are major market players, must be key actors in driving decarbonization when the appropriate interventions are utilized and therefore deserve significantly more attention in the climate policy debate. Highlights: State-owned enterprises are central to power sector decarbonization. Comparative case studies yield useful state-owned power company archetypes. Market-based climate policies are not always effective in state-led power markets. Policy targeting state-owned enterprises can accelerate power sector mitigation.